2015
DOI: 10.1093/mnras/stv241
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the temperature inhomogeneity in quasar accretion discs from the ultraviolet-optical spectral variability

Abstract: The physical mechanisms of the quasar ultraviolet (UV)-optical variability are not well understood despite the long history of observations. Recently, Dexter & Agol presented a model of quasar UV-optical variability, which assumes large local temperature fluctuations in the quasar accretion discs. This inhomogeneous accretion disc model is claimed to describe not only the single-band variability amplitude, but also microlensing size constraints and the quasar composite spectral shape. In this work, we examine … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 120 publications
(219 reference statements)
2
35
1
Order By: Relevance
“…That AGNs exhibit strong variability in a wide spectral range, covering radio, UV/optical, X-ray, and γ-ray wavelengths (Ulrich et al 1997) allows identification of AGNs on the basis of their variability properties. The onset of wide-area massive time-domain optical imaging surveys triggered a multitude of AGN variability studies with the aim of characterizing the optical variability and establishing a method for quasar selection (Kelly et al 2009(Kelly et al , 2011(Kelly et al , 2013Kozłowski et al 2010Kozłowski et al , 2011Kozłowski et al , 2012Kozłowski et al , 2013MacLeod et al 2010MacLeod et al , 2011MacLeod et al , 2012Schmidt et al 2010Schmidt et al , 2012Palanque-Delabrouille et al 2011;Butler & Bloom 2011;Kim et al 2011;Ruan et al 2012;Zuo et al 2012;Andrae et al 2013;Zu et al 2013;Morganson et al 2014;Sun et al 2014;Graham et al 2014;De Cicco et al 2015;Falocco et al 2015;Kokubo et al 2014;Kokubo 2015). These investigations confirmed the general picture that AGNs show non-periodic, stochastic flux variability occurring on timescales of several months to several years with a fractional amplitude of typically ∼10−20%.…”
Section: Introductionsupporting
confidence: 59%
“…That AGNs exhibit strong variability in a wide spectral range, covering radio, UV/optical, X-ray, and γ-ray wavelengths (Ulrich et al 1997) allows identification of AGNs on the basis of their variability properties. The onset of wide-area massive time-domain optical imaging surveys triggered a multitude of AGN variability studies with the aim of characterizing the optical variability and establishing a method for quasar selection (Kelly et al 2009(Kelly et al , 2011(Kelly et al , 2013Kozłowski et al 2010Kozłowski et al , 2011Kozłowski et al , 2012Kozłowski et al , 2013MacLeod et al 2010MacLeod et al , 2011MacLeod et al , 2012Schmidt et al 2010Schmidt et al , 2012Palanque-Delabrouille et al 2011;Butler & Bloom 2011;Kim et al 2011;Ruan et al 2012;Zuo et al 2012;Andrae et al 2013;Zu et al 2013;Morganson et al 2014;Sun et al 2014;Graham et al 2014;De Cicco et al 2015;Falocco et al 2015;Kokubo et al 2014;Kokubo 2015). These investigations confirmed the general picture that AGNs show non-periodic, stochastic flux variability occurring on timescales of several months to several years with a fractional amplitude of typically ∼10−20%.…”
Section: Introductionsupporting
confidence: 59%
“…Although it is possible to predict correlations between the variability amplitude and the AGN parameters (also an anticorrelation with λ Edd ) within the standard α-disk prescription (Shakura & Sunyaev 1973) by assuming global fluctuations ofṀ (e.g., Zuo et al 2012;Meusinger & Weiss 2013), the resulting scaling relations are much flatter than the observed ones. What is more, the typical timescales of optical variability are much shorter than the time needed for global changes of the mass accretion rate in the entire disk, associated with the sound crossing or viscous timescale (Courvoisier & Clavel 1991;Uttley & Casella 2014;Ruan et al 2014;Kokubo 2015). For this reason it is unlikely that global accretion rate changes are the sole driver of optical variability.…”
Section: Discussionmentioning
confidence: 99%
“…Since the autocovariance function is coupled to the PSD by a Fourier transform, the latter can be expressed as a weighted sum of Lorentzian functions, which are known to provide a good description of the PSDs of X-ray binaries and AGNs (Nowak 2000;Belloni et al 2002;Belloni 2010;De Marco et al 2013, 2015. The CARMA model includes the Ornstein-Uhlenbeck process or the "damped random walk", which is depicted in detail in Kelly et al (2009) and was found to accurately describe quasar light curves in many subsequent works, as the special case of p = 1 and q = 0.…”
Section: Measuring σ 2 Rms On Different Timescalesmentioning
confidence: 99%
“…While an inhomogeneous disk has been demonstrated to fit composite difference spectra (Ruan et al 2014) and color variability of quasars (Schmidt et al 2012), Hung et al (2016) find a simple disk model adequate to fit differenceflux UV/optical spectral energy distributions of individual quasars. Moreover, Kokubo (2015) argues that the tight interband correlations observed in SDSS quasar light curves are inconsistent with the inhomogeneous disk model. However, whether or not these thermal fluctuations can be coherent enough to produce a large-amplitude outburst is still to be determined.…”
Section: Accretion Disk Instabilitiesmentioning
confidence: 99%